Inattention and hyperactivity in children and adolescents with repaired D-transposition of the great arteries: Prevalence, perioperative risk factors, and clinical outcomes - Chen, Hongtong; Yan, Yichen; Li, Cong; Zheng, Xiangyu; Wang, Guanghai; Jin, Zhijuan; Shi, Guocheng; He, Xiaomin; Tong, Xiaoping; Chen, Huiwen; Zhu, Zhongqun (Frontiers in Cardiovascular Medicine, 2022)
Objective: The present study objectives were to determine the prevalence of attention-deficit/hyperactivity disorder symptoms（ADHD-like symptoms）in children and adolescent with d-transposition of great artery (D-TGA) after arterial switch operation (ASO) and examine associated risk factors and adverse personal,family dysfunctions. Methods: This cohort study included 103 patients with D-TGA who underwent ASO in early infancy at Shanghai Children’s Medical Center between 2011 and 2016 and then follow-up. Data analysis was conducted from September 2020 to April 2022.A standardized Swanson, Nolan, and Pelham IV (SNAP-IV) questionnaire is used to evaluate inattention and hyperactivity symptoms. Demographic, preoperative, intraoperative, and postoperative factor were collected. Univariate and multivariable regression analyses were performed with odds ratios (OR) and 95% confidence intervals (CIs). Results: Prevalence of ADHD-like symptoms was 27.18%(28/103). Attention-deficit (18/28 ,64.29%) symptom was the predominant subphenotype. After underwent TGA surgery, 39% of patients with ADHD-like symptoms receive remedial special academic services.There is none had repeated grade.Univariate analysis showed that, positive inotropic drug score (P=0.03) and delayed sternal closure (P=0.02) were risk factors of ADHD-like sympotoms; increased preoperative oxygen saturation (SPO2)(P=0.01) and surgical height (P=0.01) and TGA subtype (VSD )(P=0.02) were protective factor of ADHD-like sympotoms.Multivariable analysis showed that delayed sternal c losure (DSC)(OR, 1.50; 95% CI, 1.02-2.18) is a risk factor for the occurrence of ADHD-like sympotom while increased preoperative oxygen saturation (odds ratio [OR], 0.95; 95% confidence interval [CI], 0.92-0.99) is a protective factor of ADHD-like sympotom. Conclusion: The children and adolescents with D-TGA after ASO were at high risk of ADHD-like symptoms. Preoperative hypoxic status and postoperative DSC became predominant risk factors. Modification of the risk factors may be helpful to relieve ADHD-like symptoms for these patients.